The Evaluation of Online Learning Effectiveness in Economic Course - Ida Ayu Mahadewi; I Made Candiasa; Dewa Gede Hendra Divayana (Universitas Pendidikan Ganesha, 2023)
The study was conducted to evaluate the effectiveness of online learning process for economic course during covid-19 pandemic. A quantitative approach was used in this study particularly in the form of evaluation using CIPP model. There were four main components; context, input, process, and product. There were 150 participants were involved in which they were three teachers who taught economic course and 147 students who took social and economic department. They were selected by using random sampling technique. The data were collected through observation, document analysis, and questionnaire distribution. The instruments used were observation sheet, and questionnaire. The obtained data were analysed by using descriptive statistical analysis. The results showed that the online learning online learning process for economic course during covid-19 pandemic was effective with good category. The context evaluation was categorized into good category with the percentage of 72.33%. The input evaluation was also found on the percentage of 73.78% categorized into good category. The process evaluation had a good category with the percentage of 73.75%. The product evaluation was categorized into an excellent category. Those four components showed that the online learning had been conducted effectively.